PERSPEKTIF REMAJA TENTANG KESEHATAN REPRODUKSI SEBAGAI UPAYA PENCEGAHAN PENYIMPANGAN PERILAKU SEKSUAL DI KABUPATEN BEKASI - Maesaroh Maesaroh; Eka Kartikawati; Devi Anugrah (UNIVERSITAS PGRI MADIUN, 2019)
Indonesia's demographic data shows that the percentage of young people over 20% or about 60 million Indonesians is at a young age. This potential greatly determines the progress and character of the nation in the future. The swift influence of globalization through the media has a positive and negative impact on the growth and behavior development of the younger generation. One of the negative impacts facilitated by the spread through the media was deviant behavior that occurred in various parts of the world which was later imitated by young people in Indonesia. Drug abuse, sexual behavior outside of marriage and sexual orientation deviation or known as LGBT (Lesbian, Gay, Bisexual, Transgender). This study aims to detect the opinions and understanding of adolescents about the importance of healthy reproduction as an effort to prevent early sexual behavior deviations. The study population was middle school students in Bekasi Regency, as many as six sample schools were selected using the random sampling technique. The research method used is descriptive quantitative. The results showed that 70% of female adolescents in Bekasi maintain their reproductive health behaviors while 57% of men pay attention to their reproductive health behavior. The results of adolescent sexual deviation behavior from this study were as many as 10.9% of teenagers had masturbation, and there were 5.1% of teens wanting same-sex lovers.